The Influence of Gross Regional Domestic Product, Unemployment, and Population on Poverty of Cities in East Java - Salsabila, Fathiya Afini; Citra Rahayu Indraswari (Journal of Development Economic and Social Studies, 2025)
Poverty is still a widespread problem in developing countries, including Indonesia, which can occur especially in urban areas. To overcome poverty, it is necessary to understand the contributing factors and economic indicators that influence it, measured by various indicators. This study examines the impact of Gross Regional Domestic Product (GRDP), unemployment rate, and population on poverty rates in nine cities in East Java from 2017 to 2023. This study analyses how GRDP, unemployment rate, and population contribute to poverty rates in these areas over a specified period. This study uses secondary data from the East Java Central Bureau of Statistics (BPS), focusing on a sample of nine cities in the region. Using panel data analysis, the Ordinary Least Squares (OLS) method and the classical assumption test. The study results reveal a significant relationship between GRDP and, unemployment rates on poverty rates, indicating that economic growth and employment status are closely related to poverty. In contrast, population size does not show a significant effect on poverty.